ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM BERINVESTASI SUKUK NEGARA - RIZKY ADITYA, DEANDRA; Manzilati, Asfi (Islamic Economics and finance in Focus, 2023)
Sukuk is one of the sharia -based investment instruments that are experiencing an increase in Indonesia. This is inseparable from the start of the public's consciousness of investing, one of which is through sukuk especially the country's sukuk. From this phenomenon, an analysis is needed to find out the factors influence the interest of Islamic economics students at Brawijaya University in investing in the country's sukuk because besides being an Indonesian society, the Islamic Economics students of Brawijaya University also studied about sharia products in lectures so that they are relevant when research is conducted. The purpose of this research is to determine the effect both partially and simultaneously from the motivational factor, knowledge factors, and risk preference factors for student investment interest in sukuk. Technique Data collection using incidental sampling techniques or non probability sampling because of students what is studied must meet the requirements to have taken the Fiqh Muamalat course not yet clearly known. Data collection was obtained by distributing questionnaires to 82 Islamic economics students through google form. The statistical methods used are descriptive analysis and logistical regression analysis with testing hypothesis uses statistical tests t. The results of this study indicate that simultaneously, motivational factors, knowledge, and risk preferences have a positive effect on the interests of students to invest in sukuk. However, partially only motivational factors